Comparative in vitro study of the antidiabetic, anti-inflammatory, and antioxidant potential of the Piper cubeba, Piper betle, and Piper nigrum - Shreya Naga Devika C; Keerthana M.; Myrene Roselyn Dsouza; Sharangouda J. Patil; Premalatha S.J. (The Bioscan, 2024)
The study was performed in vitro to evaluate and compare the antidiabetic, anti-inflammatory, and antioxidant effects of aqueous, ethanol and methanol extracts of Piper nigrum, Piper cubeba, and Piper betle. Piper betle leaves and seeds of P. cubeba and P. nigrum were collected from different regions and analyzed for their phytochemical components. The investigation included the assessment of the total phenolic, alkaloid, flavonoid, tannin, and terpenoid contents. The antidiabetic effects of the extracts of the three species were determined through several assays, such as α-amylase inhibition, glucose adsorption capacity, and glucose uptake by yeast. The methanolic extracts exhibited significant inhibition of α-amylases, with P. cubeba showing 71% inhibition, P. betle 88%, and P. nigrum 70% at 100 mg/ml concentration. In the glucose adsorption capacity assay, the methanolic extracts of P. cubeba, P. nigrum, and P. betle demonstrated glucose adsorption rates of 39%, 38%, and 47%, respectively, from a 100 mM glucose solution. Furthermore, in the glucose uptake by yeast assay, the methanolic extracts showed a markedly higher percentage of glucose uptake compared to the other extracts, exhibiting activity similar to that of the standard acarbose. The anti-inflammatory properties were evaluated using a protein denaturation assay, which indicated that P. cubeba and P. nigrum had the highest inhibitory activities in methanol extracts, while P. betle showed significant activity in ethanol extracts. The antioxidant properties of the aqueous, methanol, and ethanol extracts were assessed, focusing on their ability to scavenge DPPH free radicals and their remarkable reductive potential towards ferric chloride ions and phosphomolybdate in the tests carried out. Importantly, the methanolic extract of P. betle leaves exhibited superior antioxidant capacity compared to the aqueous and ethanol extracts of P. cubeba and P. nigrum.